Dynamics of Changes of AChE Contents in Some Hypothalamic Nuclei after Different Periods of Food Deprivation and Regime - Temur, Atilla; Atli, Mustafa; Askerov, Fahrettin; Kadimova, Snleyman; Karadag, Hnseyin (Asian Journal of Chemistry, 2010)
The contents of acetylcholinesterase were determined by quantitative cytophotometric method in neuron organization of lateral nucleus (LN), ventro-medial nucleus (VMN), paraventricular nucleus and supraoptic nucleus of hypothalamus after different periods of food deprivation and restoration of food regime. The obtained results have shown that cholinergic mediator system of LN is responsible for the perception and switching on the central regulation mechanisms of food motivation. The neurotransmitter system of VMN is necessary for gradual realization of energetic sources of the organism.